Analysis of partial discharges in supporting insulators - D. A. Polyakov; K. I. Nikitin; N. A. Tereshchenko; A. S. Novoselov; Ya. P. Bilevich (Омский научный вестник)
The diagnostics of overhead power lines is an important issue in the modern electric power industry. Sometimes supporting insulators are destroyed by external factors. Cracks in insulators can cause the destruction of the insulator, which increases the electrical injuries of personnel. Therefore, the article investigates the diagnosis of insulators by the method of partial discharges as a tool for personnel protection. The electric field of normal and defective insulators is simulated. Partial discharges (PD) experiments are conducted in the same insulators. The results of modeling the electric field show a high electric field intensity in a porcelain insulator with a slit and in an epoxy insulator with a crack. In these cases, the electric field in the air gap is higher than the electric strength of the air. In other cases, the electric field is not exceed the electric strength of the material. Experimental studies have shown the highest intensity of partial discharges in cases of high electric field strength obtained in the simulation. However, other defective insulators also show the presence of partial discharges. The only case of the absence of partial discharges is a porcelain insulator without a defect. An analysis of experimental data shows that the diagnosis of partial discharges can be effective for insulators only if a voltage higher than the working voltage is used. In the experiments, only voltages of 16 kV and higher made it possible to reliably detect the presence of a defect. Therefore, this method cannot be recommended for the diagnosis of supporting insulators before the disconnector is used by personnel, which could reduce the electrical injuries of personnel. In addition, monitoring of partial discharges also will not be effective for the studied types of defects.